2023
DOI: 10.3390/healthcare11071026
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Reproductive Treatments, Quality of Life, and Alexithymia in Couples

Abstract: Infertility and related treatments can negatively affect a couple’s wellbeing. The aim of this study was to evaluate couples starting assisted reproductive treatment, differences in alexithymia and quality of life levels between partners, and the association of these psychological dimensions within the couple’s members. Data was collected in two fertility centres in Rome; 47 couples completed the Fertility Quality of Life (FertiQoL), the 20-item Toronto Alexithymia Scale (TAS-20), and a socio-demographic quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…A study has shown that in couples who are candidates for ART, a better quality of life in women is predicted with their partner’s more capabilities of identifying and describing emotions. It is also reported in this study that the better quality of life of each couple is related to the quality of life of the other 15 .…”
Section: Introductionsupporting
confidence: 70%
“…A study has shown that in couples who are candidates for ART, a better quality of life in women is predicted with their partner’s more capabilities of identifying and describing emotions. It is also reported in this study that the better quality of life of each couple is related to the quality of life of the other 15 .…”
Section: Introductionsupporting
confidence: 70%
“…Previous research has suggested a correlation between elevated externally oriented thinking in males relative to their partners and their QoL levels. Furthermore, the QoL of both partners appears to be intricately interconnected ( 35 ). This finding underscores the significance of implementing interventions aimed at couples as a collective unit.…”
Section: Discussionmentioning
confidence: 99%
“…Renzi et al similarly showed that men’s higher capability to identify and describe their emotions was associated with their wives’ higher quality of life 39 . It is believed that in dynamic interaction, it is indispensable for couples to make an effort to reduce their partner’s stress by using appropriate strategies 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this finding confirms the results of Casu et al 's study, which showed that the effect of couples' social support was mediated by their coping strategies 37 . Renzi et al similarly showed that men's higher capability to identify and describe their emotions was associated with their wives' higher quality of life 39 . It is believed that in dynamic interaction, it is indispensable for couples to make an effort to reduce their partner's stress by using appropriate strategies 40 .…”
Section: Discussionmentioning
confidence: 99%